Analysing the fundamental values of Islam in the planning and design of historic Nusantara-vernacular masjid architecture for regional sustainable Malay Islamic architecture - Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita; Denan, Zuraini; Abdul Rahim, Zaiton; Abdullah, Fadzidah; Ahmad Sarkawi, Azila (2019)
Masjid, as a congregational space for worship by Muslims, is expressed architecturally through a definitive building typology reflecting its assimilation to the local climate, culture and intuitive technology. While the worldview of Masjid, as a pure Islamic Architecture based on the Middle-Eastern and Indian Sub-Continent Architecture, the Malay world concept of Masjid Architecture is given an image basked in mystic and layers of culture and beliefs system inherited from the non-Islamic period. The objective of this research are (i) to define Islamic Architecture as easily understood by the stakeholders whom may be clients, decision makers, multi-users of the masjid including architects; and (ii)to investigate the Malay architectural interpretation of Islamic architecture through the vernacular-Nusantara Masjid Architecture built-form as contribution to the guidelines appropriate for masjid design in the Nusantara region. A mix-mode research methodology is adopted for this research. Primary data is acquired through deduction, interviews, observation, images and site visits to the selected sites. Secondary data is acquired through content analyses of relevant literature, images, documented and non-documented metaphor. Analyses and findings of the research through comparative and reconstructive method will enable the physical and spiritual definitions of the Malay-Muslim Nusantara architectural interpretation of submission to Allah SWT materialised with meaningful interpretation. Limitation of the research is the availability of historic masjids, the presence of knowledge participants, language and research duration. Although the Malay world includes the South-East-Asian region, for this phase of the research only selected Malaysian and Indonesian vernacular masjids will be analysed. Expected outcome of this research are (i) the definition of Islamic architecture interpreted as architectural guidelines imposed on buildings that is easily understood by stakeholders; (ii) the interpretation of Islamic Architecture extracted from vernacular-Nusantara Masjid built- form significant in the Malay World to be integrated as identity, culture and technological sustainability within the above guidelines.